Mild cognitive impairment: where does normal ageing end and where dementia begins? - Custodio, Nilton (2012)
Due to the increasing prevalence of dementia in the world we must put special attention to diagnostic evaluation of pre-dementia stages. Mild cognitive impairment (MCI) could be considered an early stage of dementia, particularly of Alzheimer's disease (AD), so we consider important proper diagnosis using reliable and sensitive tools and techniques in order to discriminate subjects with normal and pathological aging. Epidemiological studies show high prevalence of MCI in the general population as well as progression of MCI to dementia and AD, especially in subjects with amnesia type MCI. Age, APOE-ε4 carrier status, hippocampus atrophy by MRI, and presence of certain biomarkers in cerebrospinal fluid can influence conversion. Evaluation of patients with MCI suspicion should be the same used in suspicion of dementia and AD. Neuropsychological assessment is the only test confirming diagnosis and helps making a proper classification of MCI subtypes: amnesic, multidomain and non-amnesic single domain.